Internal Marketing, Concept And Application For Increased Corporate Performance - Suryati Suryati; Nadia Irhamna (UIN Raden Mas Said Surakarta, 2022)
The study explained the company's internal use of marketing, the internal impact of marketing and its elements, the internal marketing of the management of change, and its brunt on corporate performance, which has given the perspective that a company's performance can start with potent internal marketing in the company. It was explained that the in-based approach to internal marketing was not just how to communicate the company's strategy and plan to its internal customers but also many things that were part of internal marketing; however, sometimes, companies were not considered internal marketing. In addition, internal marketing also has several crucial elements that make internal marketing become successful in the company. This article's three internal marketing elements are internal market involvement, commitment, and research. Furthermore, internal marketing would affect the management of changes in the company. It was closed with a refinement of the organizational performance resulting from internal marketing